HUBUNGAN RESILLIENSI PERUBAHAN PEMBELAJARAN DARING KE LURING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Mira Marlina; Sarah Caesarani; Sarah Yulia Safitri (LPPM Universitas Bina Bangsa, 2022)
The research to determine the description of resilience, description of communication skills the relationship between learning change resilience online to offline on students' mathematical communication skills and the magnitude of the relationship of resilience to students' mathematical communication skills. This research is a quantitative research. with descriptive and correlation analysis techniques. The results showed that: 1) students' mathematical resilience abilities were able to meet the indicators; 2) students' mathematical communication skills are able to meet the indicators; 3) there is a relationship between the resilience of online and offline learning changes to students' mathematical communication skills and 4) there is a very strong positive relationship between the resilience and the mathematical communication ability